Analysis of Commercial Bank Credit Distribution on Economic Growth and Employment Absorption in Indonesia - Ginting, Andi Lopa; Widyawati, Retno Febriyastuti (Universitas Ahmad Dahlan, 2022)
The research to determine the effect of commercial bank lending on economic growth and employment absorption in Indonesia. The data sources used are BPS, Bank Indonesia, and OJK. The data collection method is using periodic report data (time series) for 2007-2017. The method is quantitative analysis, using path analysis. The results: commercial bank credit has a direct effect on economic growth; commercial bank credit has a direct effect on employment absorption; Economic growth does not directly affect employment absorption; Commercial bank credit has no indirect effect on employment absorption through economic growth.